Evaluation of Rodenticidal Baits Against Rodent Population in Long melon (Cucumis melos var. Utlissimus) Crop Fields - Kumar, Parmesh; Pashan, S C; Sabhlok, V P; Singal, R K (Annals of Arid Zone, 2016)
Single do.se anticoagulant, bromadiolone (0.005%) and acute rodenticide,zinc pho.sphide (2%) were evaluated in long melo.n fields during summer 1994 inÂ and aro.und Hisar. Do.uble baiting treatments comprising zinc phosphide andÂ bromadiolone in different combinations accomplished significantly (P